'Florida Whitewater' Caladium - A University of Florida Cultivar - G. J. Wilfert; Brent K. Harbaugh; B. D. Miranda (EDIS)
Caladiums [Caladium bicolor (Ait.) Vent., syn. Caladium xhortulanum Birdsey], grown for their colorful foliage, are members of the aroid family (Araceae Juss.) native to tropical America (Croat, 1979). Although their native habitat largely consists of dense, moist forests with heavy shade, many of the cultivars grown today retain their bright color in full sun (Bell and Wilfret, 1998). Demand for caladiums is increasing because of their diversity in leaf color and shape, adaptability to various light conditions, and relatively low maintenance requirements (Harbaugh and Tjia, 1985). 'Florida Whitewater', derived from a cross between the popular caladium cultivars 'White Wing' and 'White Queen', initially was evaluated in 1985 as GC85-338. This document is ENH964, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 25, 2003.